Seasonal succession of bacterial communities, metabolic potential and ecological functions in soy sauce wastewater treatment system. (October 2020) - Liang, Hebin; Luo, Xiaotong; Ye, Dongdong; Yan, Junwei; Luo, Lixin
Abstract: Deciphering how bacterial community respond to seasonal variation is beneficial to determine their ecological significances and maintain the performance of wastewater treatment system. Although seasonal succession patterns of bacterial community have been widely investigated, paucity information is known about whether their metabolism and functions have seasonal variations resembling bacterial communities. Here, a combination of 16S rDNA and rRNA amplicon sequencing and qPCR approaches were performed to unravel the response of bacterial community as well as their metabolic potential and functions to seasonal variation. rDNA-derived community exhibited significant seasonal distribution and remarkable divergency with rRNA-derived community, indicating that the structure of the active community was unable to reflect the total community. In addition, environmental factors, such as temperature, total ammonia nitrogen, pH, COD and nitrate concentration, showed different effects on total and active communities. Moreover, quantification of bacterial 16S rDNA and rRNA suggested that bacterial consortia in activated sludge was likely to maintain metabolic potential. Functional traits of them were dominated by chemoheterotrophy, fermentation and nitrogen cycling processes, thus ensuring the stability of this system. Although there were no significant seasonal differences in both DNA and RNA-derived functional compositions, remarkable distinctions were observed between them, indicating that only partial bacteria in activated sludge kept metabolic potential. Collectively, this work provided guidelines for detecting how metabolic potential and functions of bacterial populations in wastewater treatment system respond to environmental factors. Graphical abstract: Image 1 Highlights: Seasonal variations had remarkable effects on DNA-derived community. DNA and RNA-based community showed significant differences. Environmental factors significantly affected total and active bacterial community. Bacterial assembly maintained potential activities and stable ecological functions.